The war below : a novel - Skrypuch, Marsha Forchuk (Scholastic Press, 2018)
Luka, a Ukrainian boy working in a slave labor camp, plays dead after an explosion at the factory and escapes, eventually joining a resistance group that opposes both the Nazis and the Soviets, and through the danger of the guerilla fighting he has two overriding goals--find out if his parents are still alive, and reunite with Lida, a girl who was a friend in the labor camp.